The Stone Sources of The Takht-E-Soleyman Complex: A Reconnaissance - Hamid Amanollahi (Sustainable Earth Trends)
Although numerous archaeological studies have been carried out on the “Takht-e-Soleymān” (TS) site, a better and deeper understanding of this fire-temple complex requires more investigation and research. Petrographic analysis of the stone blocks used to construct this complex is worthwhile from several aspects: firstly, the present study particularly identifies, for the first time, the physical properties of the stone pieces (color, texture, physical strength, luster, etc.) and their petrographic characteristics in thin-section (including rock type, mineral constituents, and textures/microstructures). In addition, this study helps identify the suitable materials for protecting and repairing the stone pieces used in the construction of the “Takht-e-Soleymān complex” (TSC). By close petrographic and micropaleontological examination of rock samples collected from the ancient quarries and from the TSC complex, and through the comparison of the data, the following results were achieved: the detailed study of 12 rock samples collected from different parts of the TSC including Sassanid buildings (ramparts and towers number 4,15, 35, the northern vestibule, Anahita Temple, Fire Temple’s southern portico and the western or Khosrow portico) are comparable with those of Tepe Chāl (A and B), Kochka Barz ancient quarries. The quarries used in Ilkhanid buildings (the twelve-sided building, the four-columned building or the council hall, and the hunting palace) are comparable with rock samples from the Sur and Bābānazar Mountains. This facilitates the selection of materials for subsequent restorations.